2019
DOI: 10.3899/jrheum.180881
|View full text |Cite
|
Sign up to set email alerts
|

Disease Damage Influences Cardiovascular Risk Reclassification Based on Carotid Ultrasound in Patients with Systemic Lupus Erythematosus

Abstract: Objective.Composite scores of cardiovascular (CV) risk factors underestimate the CV risk in patients with systemic lupus erythematosus (SLE). Carotid artery ultrasound (US) was found useful in identifying high CV–risk patients with inflammatory arthritis. We assessed the effect of carotid US assessments on the CV risk stratification of patients with SLE.Methods.This cross-sectional study included 276 patients with SLE. These indices were measured: lipid profile, Systematic COronary Risk Evaluation (SCORE) risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…For this reason, this calculator could better predict subclinical atherosclerosis in patients with IBD. Our data confirm previous results reported in other inflammatory diseases such as rheumatoid arthritis [ 13 ], spondyloarthropathies [ 14 ], or systemic lupus erythematosus [ 15 ]. We believe that the inflammatory load present in patients with IBD may also be responsible for this discrepancy between scores in patients and controls.…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, this calculator could better predict subclinical atherosclerosis in patients with IBD. Our data confirm previous results reported in other inflammatory diseases such as rheumatoid arthritis [ 13 ], spondyloarthropathies [ 14 ], or systemic lupus erythematosus [ 15 ]. We believe that the inflammatory load present in patients with IBD may also be responsible for this discrepancy between scores in patients and controls.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the addition of cIMT measurement and presence of carotid plaque to the Framingham risk score improves net reclassification index for predicting CV events in the general population 45. In the cross-sectional study in patients with SLE, only 6% of patients fulfilled the definitions for high or very high risk according to the SCORE risk algorithms, but as many as 32% of patients were reclassified into a very high-risk category after ultrasound assessment 46…”
Section: Discussionmentioning
confidence: 99%
“…In this case, reclassification was independently explained by the disease activity. Likewise, in a cross-sectional study that included 276 patients with systemic lupus erythematosus, following carotid ultrasound assessment, 32% of the patients were reclassified as very high-risk category [27]. In these SLE patients, disease duration and damage were independently associated with a higher risk of reclassification.…”
Section: Discussionmentioning
confidence: 99%